Beware the recurrent 'benign' multinodular goitre. Issue 4 (28th February 2023) - Papachristos, Alexander J.; Bin Mohamed Ebrahim, Mohamed Eftal; Fuchs, Talia L.; Gill, Anthony J.; Delbridge, Leigh; Serpell, Jonathan; Sidhu, Stan B.
Abstract: Background: The diagnosis of follicular carcinoma is often difficult to make on pathological analysis, as the histological distinction from follicular adenoma rests solely on the presence of capsular or vascular invasion. Even on retrospective review of the histopathology after the disease biology has declared itself as malignant, the pathological diagnosis of malignancy may not be possible to make. Methods: We report three cases in which patients were initially diagnosed with benign follicular lesions, but re‐presented with locally recurrent disease and a subsequent malignant disease course. Results: We describe a rare entity of follicular thyroid carcinoma that demonstrates a locally recurrent and eventually metastatic disease phenotype, despite persistently benign pathological findings. Conclusion: We highlight that if local recurrence occurs in discrete anatomical tissue planes, or in the thyroid bed following open total thyroidectomy for 'benign multinodular goitre', the possibility of this rare presentation of follicular thyroid carcinoma should be considered. Abstract : Rare entity: Follicular thyroid carcinoma demonstrating a locally recurrent and metastatic disease phenotype, despite persistently benign pathological findings.